The influence of training status, age, and muscle fiber type on cycling efficiency and endurance performance - Hopker, J. G.; Coleman, D. A.; Gregson, H. C.; Jobson, S. A.; Von der Haar, T.; Wiles, J.; Passfield, L. (Journal of Applied Physiology, 2013)
The purpose of this study was to assess the influence of age, training status, and muscle fiber-type distribution on cycling efficiency. Forty men were recruited into one of four groups: young and old trained cyclists, and young and old untrained individuals. All participants completed an incremental ramp test to measure their peak O2 uptake, maximal heart rate, and maximal minute power output; a submaximal test of cycling gross efficiency (GE) at a series of absolute and relative work rates; and, in trained participants only, a 1-h cycling time trial. Finally, all participants underwent a muscle biopsy of their right vastus lateralis muscle. At relative work rates, a general linear model found significant main effects of age and training status on GE (P < 0.01). The percentage of type I muscle fibers was higher in the trained groups (P < 0.01), with no difference between age groups. There was no relationship between fiber type and cycling efficiency at any work rate or cadence combination. Stepwise multiple regression indicated that muscle fiber type did not influence cycling performance (P > 0.05). Power output in the 1-h performance trial was predicted by average O2 uptake and GE, with standardized ß-coefficients of 0.94 and 0.34, respectively, although some mathematical coupling is evident. These data demonstrate that muscle fiber type does not affect cycling efficiency and was not influenced by the aging process. Cycling efficiency and the percentage of type I muscle fibers were influenced by training status, but only GE at 120 revolutions/min was seen to predict cycling performance.